Collaborative Innovations in Feedback Provision and Their Effectiveness with ChatGPT-based Approaches for Academic Writing - Fauziah, Zahra Ardeassyifa; Ambarwati, Evi Karlina (TLEMC (Teaching and Learning English in Multicultural Contexts), 2025)
In this evolving generation, examining the educational sector, feedback has been a critical element of the educational process, helping the drill and students' performance. With the discovery of Artificial Intelligence innovations, thrilling possibilities were offered for the feedback process enhancement. This study explores the perceptions of both students and educators on the role of collaborative innovations in feedback provision when integrated with ChatGPT-based approaches in academic writing. Additionally, it examines how the incorporation of ChatGPT in collaborative feedback settings influences student engagement and writing development, considering perspectives from both groups. This study utilizes a narrative review approach of 44 studies, 39 of which are highly relevant, to examine ChatGPT's role in feedback mechanisms. It highlights strengths in personalized feedback and limitations in complex interactions. as the primary source of data collection. The literature review reveals that incorporating ChatGPT into feedback processes, as viewed by both students and educators, provides significant benefits such as enhanced accessibility, improved efficiency, and personalized technical assistance, while also highlighting limitations in handling complex or nuanced interactions. However, it also presents challenges, such as the risk of students becoming overly dependent on AI and the tool's limitations in addressing conceptual aspects of writing. Therefore, ChatGPT and feedback mechanisms are likely to remain integrated into academic writing processes for the time ahead. Keywords: Academic Writing, AI, ChatGPT, Collaborative Innovations, Feedback